Implementing physiotherapy services into fistula care at Panzi Hospital, Bukavu, DRC - Keyser, LE; McKinney, JL; Mukwege, CH; Mukwege, D; Kinja, Rachel (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To describe implementation of physiotherapy services in the context of fistula care and report early program observations. Methods: Process evaluation of treatment pathway/protocol implementation and presentation of provider observations of treatment results since January 2016. Results: Dedicated physician, nursing, social work and physiotherapy staff provide various aspects of rehabilitative care to women with fistula, pre- and post-operatively. Following variations in hospital census, 5-50 women participate in group exercise sessions 2-3x/week. Targeted individual physiotherapy is selectively provided to 1-15 women 1-5x/week. Staffing priorities reflect perceived importance and impact of physiotherapy services. Providers offer clinical observations of program successes, including improved post-surgical functional outcomes, and express interest in further training to cultivate advanced clinical skills. Conclusions: Early results indicate value of physiotherapy-informed care in a comprehensive approach to fistula care services. Improving and expanding upon these skills may prove equally useful in addressing the physical impairments associated with other reproductive morbidities, such as POP. In the future, systematic use of standardized tools, such as WHODAS 2.0 is recommended, both to quantify the burden of disability in this population, as well as to measure change with therapeutic interventions, including surgery and rehabilitation.